The formation of the "Language Sub-Commission"of the Union of Gypsies-Roma (1969-1973) for Romani language standardization - Závodská, Milada (Romano džaniben, 2021)
The author reports on the "Language Sub-Commission" of the Union of Gypsies-Roma (UGR), a linguistic team systematically working – for the first time, as far as is known – on the notation of Romani in Czechoslovakia. The materials that arose through its activities identified in the collections of the Moravian Land Archive and the Museum of Romani Culture, are significant counterpoints to the Romani-language texts that are known to date, especially those that have been published in Románo ľil, the bulletin of the UGR (1970–1973). Until now authors mentioning the work of the sub-commission drew from material (solely) comming especially from Doc. Milena Hübschmannová (1933–2005), its former member. The discussed documents thus also facilitate the contextualization of the role played by Hübschmannová, the founder of Czech Romani Studies, in the process of Romani language standardization. Last but not least, the paper highlights the importance of native speakers of Romani to this process, especially Antonín Daniel (1913–1996) and Andrej Pešta (1921–2009), who had been using their mother tongue in writing for many years prior to the birth of the UGR, as well as Bartoloměj Daniel (1924–2001) and others involved in the work for the periodical Románo ľil, or contributing with their own texts in Romani to that periodical.